Detection of Salmonella Typhimurium in the Milk of a Cow with Mastitis: A Red Alert for Reproductive Health and Food Safety - Selda Beker; Serpil Kahya Demirbilek (Erciyes Üniversitesi Veteriner Fakültesi Dergisi, 2026)
This case report describes the microbiological isolation and characterisation of Salmonella enterica serovar Typhimurium (4,12:i:1,2) from the milk of a six-year-old Holstein cow with chronic mastitis and infertility. Milk and faecal samples collected during a farm investigation were subjected to bacteriological analysis in accordance with FDA and ISO standards, respectively. The isolate was identified using the BD PhoenixTM 100 automated system and subsequently serotyped at the Etlik Veterinary Control Central Research Institute. Molecular confirmation was performed by detecting the invA gene, and antimicrobial susceptibility was assessed by disc diffusion. This report documents a rare microbiological finding of S. Typhimurium in milk, highlighting milk as a potential source of transmission and emphasising the importance of comprehensive microbiological surveillance in dairy herds.